UTILIZATION OF MARINE RESOURCES AS INDONESIAN LANGUAGE LEARNING MATERIAL: TEACHERS' PERSPECTIVES - Mega Puspitasari; Bohri Rahman; Na' Imatul Izza Amalia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
The urgency of this research lies in the fact that the utilization of the marine ecosystem in the Sreseh area is still not optimal in supporting SDG number 14, which is life below water (marine ecosystems), emphasizing the protection and sustainable use of marine resources. One solution that can be implemented is to integrate the potential of the local marine resources in Sreseh into Indonesian language learning materials. This research aims to describe teachers' perspective regarding the utilization of marine resources as Indonesian language learning material. The research location is Sreseh District, Sampang Regency. The research subjects are Indonesian language teachers at SMAN 1 Sreseh. The data collection technique used was a teacher response questionnaire. The data obtained were analyzed using interactive analysis techniques including data collection, data condensation, data display, and conclusion drawing or verification. The research results indicate that the application of marine resources as learning material has never been done, and text containing the potential of marine resources is needed for contextual learning.